Kinetic study of dry anaerobic co-digestion of food waste and cardboard for methane production. (November 2017) - Capson-Tojo, Gabriel; Rouez, Maxime; Crest, Marion; Trably, Eric; Steyer, Jean-Philippe; Bernet, Nicolas; Delgenès, Jean-Philippe; Escudié, Renaud
Graphical abstract: Highlights: Lower methane yields were obtained at increasing substrate loadings. Higher TS contents caused longer lag phases but did not affect methane yields. Cardboard addition alleviated the initial VFA accumulation and pH drop. Propionic acid was the last VFA to be degraded. Higher amounts of soluble organic matter remained undegraded at higher loads. Abstract: Dry anaerobic digestion is a promising option for food waste treatment and valorization. However, accumulation of ammonia and volatile fatty acids often occurs, leading to inefficient processes and digestion failure. Co-digestion with cardboard may be a solution to overcome this problem. The effect of the initial substrate to inoculum ratio (0.25 to 1 gVS·g VS −1 ) and the initial total solids contents (20–30%) on the kinetics and performance of dry food waste mono-digestion and co-digestion with cardboard was investigated in batch tests. All the conditions produced methane efficiently (71–93% of the biochemical methane potential). However, due to lack of methanogenic activity, volatile fatty acids accumulated at the beginning of the digestion and lag phases in the methane production were observed. At increasing substrate to inoculum ratios, the initial acid accumulation was more pronounced and lower cumulative methane yields were obtained. Higher amounts of soluble organic matter remained undegraded at higher substrate loads. Although causing slightly longer lag phases, high initial total solids contents did not jeopardize the methane yields. Cardboard addition reduced acid accumulation and the decline in the yields at increasing substrate loads. However, cardboard addition also caused higher concentrations of propionic acid, which appeared as the most last acid to be degraded. Nevertheless, dry co-digestion of food waste and cardboard in urban areas is demonstrated as an interesting feasible valorization option.